Monthly prediction of drought classes using log-linear models under the influence of NAO for early-warning of drought and water management - Moreira, Elsa (2019)
SFRH/BPD/99757/2014 This work was partially supported by the projects IMDROFLOOD-Improving Drought and Flood Early Warning, Forecasting and Mitigation using real-time hydroclimatic indicators (WaterJPI/0004/2014) and project UID/MAT/00297/2013 (Centro de Matematica e Aplicacoes), both funded by funded by Fundacao para a Ciencia e a Tecnologia, Portugal (FCT). Ana Russo thanks also FCT by the Post-Doc research grant SFRH/BPD/99757/2014.